Adaptation and Validation of a Test for the Evaluation of Tactical Knowledge in Soccer: Test de Conocimiento Táctico Ofensivo en Fútbol for the Brazilian Context (TCTOF-BRA) - Rechenchosky, Leandro; Menegassi, Vanessa Menezes; Jaime, Matheus de Oliveira; Borges, Paulo Henrique; Serra-Olivares, Jaime; Rinaldi, Wilson (Frontiers in Psychology, 2022)
Background: Studies and tests to assess the tactical domain of young soccer players are recent and few instruments meet the majority of quality criteria. Objective: To adapt and validate the Test de Conocimiento Táctico Ofensivo en Fútbol (TCTOF) for the Brazilian context (TCTOF-BRA). Methods: The article consists of two studies. Study 1 (n = 111) included the translation, theoretical/semantic analysis, back translation, cross-cultural equivalence, and content and face validity (pre-test). In study 2 (n = 768), a theoretical and empirical item analysis was carried out, followed by construct validity (exploratory factor analysis, confirmatory factor analysis, and the known-groups method) and reliability (internal consistency and repeatability). Results: In the cross-cultural evaluation, the CCVt of the instrument was 0.96 and in the content validity, the CCVt of the instrument was 0.87. The face validity was confirmed (> 95%). After theoretical and empirical analysis, 15 questions were included in the Teste de Conhecimento Tático Ofensivo no Futebol (TCTOF-BRA). The exploratory factor analysis showed a model with adequate fit (KMO = 0.69; Bartlett p < 0.001), with a factor structure considered very good, composed of four factors (decision making, operational tactical principles, collective tactical-technical elements, and rules). The confirmatory factor analysis by the Asymptotically Distribution-Free estimation method demonstrated good and very good goodness of fit indices (X2/df = 1.54, GFI = 0.99, CFI = 0.94, TLI = 0.92, PGFI = 0.71, PCFI = 0.76, RMSEA = 0.03, ECVI = 0.26). The known-groups method showed significant differences (p < 0.01) and effect sizes varying from small-to-medium to large. With respect to reliability, coefficients of 0.89 (CR) and 0.74 (KR20) for internal consistency and 0.85 for repeatability were found. Conclusion: The TCTOF-BRA presented satisfactory evidence, demonstrating it to be an instrument with valid and reliable measures for the evaluation of tactical knowledge (declarative and theoretical procedural), based on specific knowledge and decision making (cognitive domain), of Brazilian young soccer players from 12 to 17.9 years old.